1986
DOI: 10.1164/arrd.1986.134.5.1040
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Type IStreptococcus pneumoniaeto Tracheal Epithelium of Mice Infected with Influenza A/PR8 Virus1–3

Abstract: Bacterial adherence to virus-infected respiratory tract cells may be one of the several mechanisms whereby virus predisposes to bacterial pneumonia. To evaluate the effect of influenza virus infection on pneumococcus adhesion, 39 mice were infected with PR8/A influenza virus. The adherence of radiolabeled pneumococcus to mice tracheal cells was determined 2, 4, and 6 days after viral inoculation. The pneumococcal adhesion to infected tracheas was significantly enhanced on Day 6 (p less than 0.001). Scanning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
5

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 34 publications
(33 reference statements)
4
147
0
5
Order By: Relevance
“…Raman et al (1983) observed that cells from smokers bind more S. pneumoniae than those from nonsmokers. Plotkowski et al (1986) showed that prior influenza virus infection enhanced the adherence of S. pneumoniae to the tracheal epithelium of mice. Though Selinger and Reed (1979) proposed that the ability of S. pneumoniae to adhere to oropharyngeal cells might not be associated with virulency, Andersson et al (1981), have suggested that adherence of S. pneumoniae to oropharyngeal cells is an important step in the pathogenesis of otitis media, since this organism adhered avidly to pharyngeal cells from otitis media patients in an in vitro assay.…”
Section: Discussionmentioning
confidence: 99%
“…Raman et al (1983) observed that cells from smokers bind more S. pneumoniae than those from nonsmokers. Plotkowski et al (1986) showed that prior influenza virus infection enhanced the adherence of S. pneumoniae to the tracheal epithelium of mice. Though Selinger and Reed (1979) proposed that the ability of S. pneumoniae to adhere to oropharyngeal cells might not be associated with virulency, Andersson et al (1981), have suggested that adherence of S. pneumoniae to oropharyngeal cells is an important step in the pathogenesis of otitis media, since this organism adhered avidly to pharyngeal cells from otitis media patients in an in vitro assay.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza infection is known to increase adherence of and subsequent colonization with bacterial respiratory pathogens. Bacteria may adhere to the basal membrane after disruption of the airway epithelial layer by the cytopathic effect of the virus (8). It has also been suggested that the increased adherence is due to up-regulation of receptors involved in the attachment of these bacteria (9).…”
Section: Il-10 Is An Important Mediator Of the Enhanced Susceptibilitymentioning
confidence: 99%
“…142 IAV replication in the respiratory epithelium leads to impairment of mucosalciliary clearance and increased bacterial colonization. 143,144 Secondary infections primarily coincide with resolution of inflammation and the onset of reparative responses rather than early viral replication, 142,145,146 indicating host responses also have a significant effect on the susceptibility to bacterial superinfection. In experimental models the release of type I interferons and IFN-during viral clearance from the lung negatively affects the ability of lung-infiltrating neutrophils and macrophages, respectively, to control bacterial infection.…”
Section: Respiratory Tract Virus-associated Sequelaementioning
confidence: 99%